CONTENT VISUALIZATION OF ITE LAW FOR LEARNING PROCESS - Ketut Agustini; I Made Putrama; Ratna Artha Windari; Wayan Natta Maruta (Fakultas Seni Rupa dan Desain ITB, 2020)
The Information and Electronic Transaction laws (ITE Law) in Indonesia is still in the form of text and has not been effective in its dissemination, hence it is less attractive to the public, especially young Internet citizens. For this reason, there needs to be a medium as a learning tool to understand the ITE Law. This study aims to visualize the contents of the ITE Law into an interesting learning media. The development model used is Multimedia Development Life Cycle (MDLC). The subjects of this study were students of Ganesha University of Education who were interested in studying the ITE Law. From the experts' point of view, the content of this study is deemed valid, the media practical; the normality test obtained N-Gain value of 0.71, which is a high category. This study tested 20 respondents, resulting in 40% or very high responses and 60% high responses. These results indicate that the content visualization of the ITE Law is valid, practical and effective for learning. This application is expected to be able to increase the understanding of Undiksha students of the IET Law so that they can behave wisely and smartly on social media.